تقييم جودة إدارة الدراسة والتصميم للمشاريع الهندسية بالاعتماد على وظائف العملية الإدارية (دراسة حالة: الشركة العامة للدراسات والاستشارات الفنية – فرع المنطقة الساحلية) - ميّا رنا; أحمد ديما مُنيف (Latakia University Journal -Engineering Sciences Series, 2019)
Studying and designing any construction project is The Basic Phase of it, which significantly affects the following Phases, and specifies the commitment to the contractual period and implementation according to the budget set. The low quality of engineering studies leads to the poor performance of the project as a whole. In this research, the main factors affecting the quality of the design were determined. They were (51) factors, incorporated into a measurement model to test the quality of the completion of designs and studies carried out by the company representing the case study. The factors were distributed within (15) groups divided into four sections depending on their relevance to the core administrative functions. The measurement model was applied to (22) project either study or audit. According To our Search, we found the most important factors influencing the quality of the study, showing a significant area of its improvement, and they are the factors related to the duties of the owner due to the absence of effective communication mechanism between the study body and the owner of the project, in addition to monitoring the design documents and controlling its changes, due to the lack of accurate and effective documentation within the company. A number of necessary procedures have been proposed in this research to improve the quality management of the study and design of the engineering projects based on the administrative functions, which through its application constitutes the first step towards the system of improving and upgrading the quality of engineering designs and studies. تُعتبر مرحلة الدراسة والتصميم لأي مشروع إنشائي هي المرحلة الأساسية التي تؤثر بشكل كبير فيما يليها من مراحل، وتُحدّد الالتزام بالمدة العقديّة والتنفيذ وفقاً للميزانية الموضوعة. حيث ينعكس انخفاض جودة الدراسات الهندسية على أداء المشروع ككل. تمّ في هذا البحث تحديد العوامل الرئيسية المؤثرة على درجة جودة التصميم وقد بلغت (51) عاملاً، وأُدرجت ضمن نموذج قياس لجودة إنجاز التصاميم والدراسات المُنفذة من قِبل الشركة المُمثلة لحالة الدراسة. وُزعت العوامل ضمن (15) محور صُنِّفت إلى أربع أقسام تِبعاً لارتباطها بوظائف العملية الإدارية الأساسية. طُبّق نموذج القياس على (22) مشروعاً ما بين دراسة وتدقيق. توصلنا في البحث إلى أهم العوامل تأثيراً على تحديد جودة عملية الدراسة والتي تبيّنَ وجود مجال كبير لتحسينها وهي العوامل المُتعلقة بواجبات الجهة المالكة بسبب غياب آلية التواصل الفعّال بين الجهتين الدارسة والمالكة للمشروع، وإضافةً إلى ضبط وثائق التصميم والسيطرة على تغييراته وذلك نتيجةً لغياب التوثيق الدقيق والفعّال ضمن الشركة. تم من خلال هذا البحث اقتراح مجموعة من الإجراءات اللازمة والضرورية لتحسين جودة إدارة عملية الدراسة والتصميم للمشاريع الهندسية بالاعتماد على وظائف العملية الإدارية، والتي من خلال تطبيقها تُشكل الخطوة الأولى في نظام تحسين ورفع درجة جودة الدراسات والتصاميم الهندسية.